2019
DOI: 10.1111/rda.13396
|View full text |Cite
|
Sign up to set email alerts
|

Luteal vascularity and embryo dynamics in mares during early gestation: Effect of age and endometrial degeneration

Abstract: Contents The present study characterized the luteal status and the dynamic of the conceptus during the first 20 days of gestation in mares with different ages and degrees of endometrial degeneration. Total area of the corpus luteum (CL), luteal vascularity, CL area with blood signals, progesterone concentrations (P4), embryonic vesicle diameter, number of embryonic location changes, embryonic fixation position and uterine contractility were evaluated. In Experiment 1, mares ≤6 years of age (Young group, 5.6 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Their inhibition is detrimental for embryo development 87 . Thus, both reduced ATP production and disturbed ion channels’ function may impact embryo growth, although effects of mares’ age on embryo growth are controversial 2428 .…”
Section: Discussionmentioning
confidence: 99%
“…Their inhibition is detrimental for embryo development 87 . Thus, both reduced ATP production and disturbed ion channels’ function may impact embryo growth, although effects of mares’ age on embryo growth are controversial 2428 .…”
Section: Discussionmentioning
confidence: 99%
“…Disagreeing with Lemos et al (2018), age was not a factor that influenced none of the indices that evaluated in the study. As demonstrated by Ferreira et al (2019), the newly formed CL in old mares undergoes compensatory structural remodelling to ensure local blood supply and continuous P4, which maintain during early pregnancy without being influenced by the age effect. Also, we believe that age has not influenced these mares either, due to the use of balanced feed that meets the needs of embryo-receiving mares and the fact that the mares included in elderly mare group is not in the extreme within the category, not presenting worthy circulatory changes that would cause greater problems pregnancy within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a reduced quantity of mitochondrial DNA, but not genomic DNA, has been reported in Day 7 blastocysts from mares older than 16 years of age compared to younger counterparts, suggesting a reduction in mitochondria/cell ratio in old mares’ blastocysts [ 23 ]. Taken together, these alterations could lead to the alterations in embryo mobility and/or day of fixation that have been observed in some studies [ 9 , 28 ].…”
Section: Introductionmentioning
confidence: 89%
“…The effect of maternal age on embryo size is not so clear, as studies demonstrated a reduction of embryo diameter in old mares at several developmental stages [ 24 28 ] while others did not detect any effect [ 9 , 13 , 25 , 29 ] of maternal aging on embryo size. In these studies, however, the developmental stage was not uniform and the method to measure embryo size could be different (direct measurement or using ultrasonography).…”
Section: Introductionmentioning
confidence: 99%